PENGGUNAAN MEDIA APEL HURUF DALAM MENGATASI KESULITAN MEMBACA TERHADAP SISWA KELAS RENDAH SEKOLAH DASAR - Sari, Fitriana Anggun; Minsih, Minsih (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
This research was motivated by several elementary school students who had difficulty reading and that learning media could act as a tool to aid these learning delays. The aim of this research is to describe the importance of effective learning media on apple letters to improve reading fluency in lowed class elementary school student. This method used qualitative research metods. The type of qualitative research used in this research is a case study type of research by means of observation, interviews, and documentation to obtain accurate research final data. The final data can be ascertained to be accurate because it has been proven by face to face observation activities on lower grade elementary school students who have difficulty reading, apart from that, observations were also made on teachers who used the letter apple teaching media as a teaching aid supported by documentation. The teacher’s importance to improving the reading fluency of lowed class student is by using learning media in the form of letters as a tool to convey the material. Form of student reading difficulties include difficulty distinguishing letter shapes and difficulty spelling letters and words. This research obtained results thar the apple letter media is very important to help teachers improve the reading fluency of lowed class elementary school students. Apple letter media can also improve student achievement, train critical thinking, and can increase student activity in learning because when students have difficulty reaing it will disrupt their learning activities. The impact or consequence of using letter apple media or other learning media in helping overcoming reading difficulties for lowed grade elementary school students is the creation of more advance education because using teaching media aims to help students achieve their learning goals so that students will get better achievement result good.